Skin Susceptibilty to Antibiotic Contact Allergy or Irriatation? - Ali Al-Hadithi, Amal Hamadah (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2008)
The clinical manifestations of hypersensitivity in 20 patients, working in an antibiotic industry in contact with antibiotic powder were studied immunologically. Statistica analysis of the data by using Chi-square shows highly signifcant increase in the level of (IgG, IgM, IgA and IgE) Antibodies than the normal ranges(table1, figures 1, 2 and 3). It was concluding that increased reactivity to an antibiotic powder most likely reflects an allergic response rather than, increased genuine skin susceptibility.